PENGARUH FAKTOR INTERNAL TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA - Ria Andrianie; Rachmani Rachmani (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
This study aims to analyze the internal factors that influence the financial performance of Islamic Commercial Banks in Indonesia. In this study, financial performance is measured using Return On Assets (ROA). The independent variables in this study are Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Financing To Deposit Ratio (FDR). The population in this study are all Islamic commercial banks in Indonesia for the 2017-2021 period. The total sample in this study is 8 Islamic commercial banks. The data analysis technique used in this study is multiple linear regression analysis.